Herfsttij der Middeleeuwen : Studie over levens- en gedachtervormen der veertiende en vijftiende eeuw in Frankrijk en de Nederlanden - Huizinga, Johan, 1872-1945 (Salt Lake City, UT : Project Gutenberg, 2005)
"Herfsttij der Middeleeuwen" by Johan Huizinga is a historical study published in 1919. Examining fourteenth and fifteenth-century France and the Netherlands, Huizinga argues that the excessive formality and romance of late medieval court life served as a defense mechanism against society's increasing brutalization. Drawing on chronicles and literature rather than archival documents, this groundbreaking work pioneered cultural and mentality history, evoking an entire era's atmosphere in literary style. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Autumn_of_the_Middle_Ages Wikipedia page about this book: https://nl.wikipedia.org/wiki/Herfsttij_der_Middeleeuwen
Release date is 2005-10-08
Produced by Anne Dreze and Marc D'Hooghe
Keywords: Civilization, Medieval; France -- Social life and customs; Middle Ages; Netherlands -- Social life and customs